Strategic Decisions Concerning Subsidiaries and Affiliates in a Group of Companies: Computational Analytical Tools. - IUDINA, Svetlana Valentinovna; TSOVMA, Denis Vladimirovich (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Methodologically, the authors and their colleagues’ employ their proposed model of strategic decision-making in groups of companies, which allows one to integrate several critical managerial functions, set clear efficiency criteria for future decisions considering the static and dynamic state of a subsidiary and forecast the development of a group of companies with a view of long-term stable growth of its overall consolidated value and goodwill. This paper offers a systematisation and logical interpretation of indicators transforming the previously published theoretical model as a practical tool approbated on initial empirical evidence. RESUMEN Metodológicamente, los autores emplean su modelo de toma de decisiones estratégicas y el de sus colegas en grupos de empresas, lo que permite integrar varias funciones gerenciales críticas, establecer criterios claros de eficiencia para decisiones futuras considerando el estado estático y dinámico de una subsidiaria y pronóstico El desarrollo de un grupo de empresas con miras a un crecimiento estable a largo plazo de su valor consolidado general y buena voluntad. Este artículo ofrece una sistematización e interpretación lógica de indicadores que transforman el modelo teórico previamente publicado como una herramienta práctica aprobada en evidencia empírica inicial.